Factors influencing the generation of teachers’ emotions - Lai, Lihua; Shi, Wenjiang; Xie, Yi; Zhao, Jin (Frontiers in Psychology, 2024)
Background and aim The teaching profession plays an important role in shaping individuals’ lives, with teachers performing complex emotional labour. The management of emotions is an integral part of teachers’ professional work, and it is essential to clarify their emotional experiences and the generating of their emotions within a specific cultural context. Methods Based on a phenomenological approach and the use of anecdotal texts, this study examined six common emotional states among teachers, including happiness, guilt, worry, fear, annoyance, and anger, along with the emotional experiences of two specialised categories of teachers, class supervisors, and pre-service teachers. The factors influencing teachers’ emotions and their generative mechanisms were analysed. Results and discussion This investigation found that key influences on teachers’ emotions stem from factors within the teachers’ themselves, the contextual nature of their work, and sociocultural dynamics. Drawing on the analytical frameworks of emotional geography theory, ecological theory of human development, and the ecosystem model of teachers’ emotional interactions, the study constructs a model highlighting the generative mechanisms of teachers’ emotions, and in which three systems are reflected. Conclusion Teachers’ personal attributes are in the direct area of the model and directly govern the formation of their emotions, while their work context consists of a transitional area in emotion formation and the sociocultural system acts as the latent band influencing emotion development. The mechanism model helps us to understand and recognise teachers’ emotions and to explore their pedagogical implications.